2015
DOI: 10.1038/srep18450
|View full text |Cite
|
Sign up to set email alerts
|

An ancestral host defence peptide within human β-defensin 3 recapitulates the antibacterial and antiviral activity of the full-length molecule

Abstract: Host defence peptides (HDPs) are critical components of innate immunity. Despite their diversity, they share common features including a structural signature, designated "γ-core motif". We reasoned that for each HDPs evolved from an ancestral γ-core, the latter should be the evolutionary starting point of the molecule, i.e. it should represent a structural scaffold for the modular construction of the full-length molecule, and possess biological properties. We explored the γ-core of human β-defensin 3 (HBD3) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 68 publications
(128 reference statements)
6
56
1
Order By: Relevance
“…Thus, the tail of hBD‐3 (RES22‐45) is more flexible than other regions of hBD‐3. That can agree with the experimental findings from Nigro et al, who found that the γ ‐core motif of hBD‐3 (which corresponds to RES22‐45 of full length hBD‐3) had very flexible structure in neutral pH solvent, while hBD‐3 in whole had relatively rigid structure.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, the tail of hBD‐3 (RES22‐45) is more flexible than other regions of hBD‐3. That can agree with the experimental findings from Nigro et al, who found that the γ ‐core motif of hBD‐3 (which corresponds to RES22‐45 of full length hBD‐3) had very flexible structure in neutral pH solvent, while hBD‐3 in whole had relatively rigid structure.…”
Section: Discussionsupporting
confidence: 92%
“…Nigro et al worked on the disulfide bond forming pathway of reduced hBD‐3 (with 6 cysteine residues alkylated) in oxidizing condition. They found that Cys23‐Cys41 and Cys18‐Cys33 formed disulfide bonds almost simultaneously in oxidizing condition, while the Cys11‐Cys40 pair formed disulfide bond lastly.…”
Section: Discussionmentioning
confidence: 99%
“…β-Defensins are not characterized as exhibiting direct anti-protease activity; however, this has been reported for neutrophil α-defensins (Van Wetering et al., 1997) and other antimicrobial proteins including SLPI and elafin (Moreau et al., 2008, Williams et al., 2006). Furthermore, hBD2 and hBD3 contain an evolutionarily conserved “gamma-core” structural motif sufficient for antimicrobial activity and, interestingly, also for resistance to proteolytic degradation (Nigro et al., 2015). The significance of these structural features with respect to protection against V8 protease remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the potency of the γ‐core is comparable with the full‐length peptide across this whole spectrum of properties, and the peptide is not toxic to human cells. Remarkably, the peptide folds very rapidly in human serum, where it remains stable for a prolonged period of time .…”
Section: Discussionmentioning
confidence: 99%
“…Like full‐length HBD3, Peptide γ displayed potent antibacterial activity against gram‐negative ( Escherichia coli and Pseudomonas aeruginosa ) and gram‐positive ( Staphylococcus aureus ) bacteria, as well as antiviral activity against HIV and HSV . Notably, the disulfide bridge was important for the antiviral but not for the antibacterial activity, paralleling the SAR observed for HBD3.…”
Section: Introductionmentioning
confidence: 93%